The Effect of A Chatgpt-Assisted Problem-Based Learning Model on Digital Literacy Skills and Learning Outcomes of Eleventh-Grade Senior High School Students - Tasya Putri Hendrika; Laila Badriyatul Habibah; Iftinan R Azzah S (Yayasan Al Hidayah, 2026)
This study was motivated by students’ low levels of digital literacy and learning outcomes resulting from limited active engagement in the learning process. The study aimed to examine the effect of a ChatGPT-assisted Problem-Based Learning (PBL) model on the digital literacy skills and learning outcomes of eleventh-grade senior high school students. A quantitative approach with a quasi-experimental nonequivalent control group design was employed. The participants consisted of two groups: an experimental group that received ChatGPT-assisted PBL and a control group that received PBL without ChatGPT. Pretest results indicated that the initial abilities of both groups were relatively equivalent. Following the intervention, the experimental group achieved a higher posttest mean score (87.50) than the control group (81.30). The Independent Samples t-test revealed a statistically significant difference between the two groups (p < 0.05). N-Gain analysis showed a moderately effective improvement in the experimental group (65.3%) and a low improvement in the control group (38.7%). These findings indicate that integrating ChatGPT into PBL is effective in enhancing students’ digital literacy and learning outcomes in line with the demands of twenty-first-century education.